Liraglutide-Induced Hemorrhagic Pancreatitis in a Nondiabetic Patient. Issue 5 (6th May 2020) - Dolan, Russell D.; Bazarbashi, Ahmad Najdat; Lo, Amy; Smith, Benjamin N.
ABSTRACT: Liraglutide is a glucagon-like peptide 1 (GLP-1) analog with a primary effect of increased glucose-dependent insulin secretion and decreased gastric emptying. It serves as a feasible medical weight loss option because of the drug's effect of invoking satiety and lowering caloric intake. Despite emerging efficacy, the GLP-1 class has been associated with severe, although rare, adverse events, including pancreatitis. Previous investigations demonstrated the greatest association between GLP-1 agonist-associated pancreatitis in diabetic populations; however, liraglutide dosing is higher in weight loss formulations, placing the weight loss population at higher risk. We present a case of liraglutide-induced acute pancreatitis in a patient without diabetes.